Self-reference and logical memory in Hegel's theory of the concept - Magri, Elisa (Revista Eletrônica Estudos Hegelianos, 2016)
ABSTRACT: As Hegel often said, memory is essentially related to thinking. In this paper I will argue that memory plays a crucial role into the Science of Logic as well, although it does not stand for a psychological faculty. I will proceed as follows: first, I will briefly mention the relevance of memory in the Philosophy of Subjective Spirit, then I will reconstruct the correspondence between the psychological transition from Vorstellung to Denken and the speculative Übergang from Wesen to Begriff. Lastly, I will hint at the difference between self-relation and self-consciousness, focusing on the importance of the first in the Science of Logic. RESUMO: Como Hegel disse muitas vezes, a memória está essencialmente relacionada com o pensamento. Neste artigo pretende-se argumentar que a memória tem um papel decisivo também na Ciência da Lógica, apesar de aqui ela não representar nenhuma faculdade psicológica. Procede-se nos seguintes passos: Primeiro, será brevemente lembrada a relevância da memória na Filosofia do Espírito Subjetivo. Depois, será reconstruida a correspondência entre a passagem psicológica da representação ao pensamento com a passagem especulativa da essência ao conceito. Finalmente será apontada a diferença entre auto-relação e auto-consciência, focalizando a importância da primeira na Ciência da Lógica.